HUBUNGAN PUBLIC SPEAKING DENGAN PEMAHAMAN PASIEN RADIOGRAFI PANORAMIK DI RSUD SYARIFAH AMBAMI RATU EBU BANGKALAN - Az Zahra, Amelia; kusumawardani, Winda; Wahjuningdiah, Ero; Putri, Berliana Devianti; Karnoto, Karnoto; Muhaimin, Muhaimin (Dentin, 2025)
ABSTRACT Background: Panoramic radiography is an imaging examination used to visualize the teeth and oral cavity using X-rays. This examination requires proper patient positioning and clear instructions to prevent imaging errors, such as the appearance of artifacts. Providing effective instructions can be initiated through good public speaking skills. Effective communication between radiographers and patients is essential to achieve optimal image quality. Radiographers who deliver clear instructions and explanations can assist patients in understanding the examination procedures they will undergo. Objective: This study aimed to analyze the relationship between public speaking indicators—respect, empathy, audible, clarity, and humble—and patient understanding during panoramic radiographic examinations. Methods: Data were collected using a questionnaire completed by outpatients undergoing panoramic radiography. The data were then statistically analyzed using the chi-square correlation test. Results: Based on the correlation analysis between public speaking and patient understanding, among the five indicators of effective communication (respect, empathy, audible, clarity, and humble), two indicators showed a significant relationship with patient understanding (p-value < 0.05), while the remaining three indicators had p-values > 0.05, indicating no significant relationship. Conclusion: Most respondents were aged 21–30 years and were female, and they perceived radiographer communication as effective with a generally good level of patient understanding. The chi-square test results demonstrated that the clarity and humble indicators had a significant relationship with patient understanding, whereas respect, empathy, and audible showed no significant association. Keywords : panoramic radiography, patient understanding, public speaking ABSTRAK  Latar Belakang:Radiografi panoramik merupakan pemeriksaan untuk melihan gigi dan rongga mulut menggunakan sinar X. pemeriksaan radiografi panoramik memerlukan pemosisian dan isntruksi yang tepat agar tidak terjadi kesalahan foto seperti munculnya artefak. Pemberian instruksi yang baik dapat dimulai dengan public speaking. Komunikasi yang efektif antara radiografer dan pasien diperlukan agar mencapai tujuan yaitu hasil foto yang baik. Radiografer yang memberikan instruksi dan penjelasan dengan baik dapat membantu pasien dalam memahami prosedur pemeriksaan yang akan dilakukannya. Tujuan: Penelitian betujuan untuk menganalisis hubungan public speaking indikator respect, empathy, audible, clarity, humble dengan pemahaman pasien saat pemeriksaan radiografi panoramik. Metode: Pengambilan data menggunakan kuisioner yang diisi oleh pasien rawat jalan radiografi panoramik yang kemudian hasilnya diolah secara statistika menggunakan uji korelasi chisquare. Hasil: Berdasarkan hasil uji korelasi antara public speaking dengan pemahaman pasien, diketahui dari lima indicator komunikasi efeltif (respect, empathy, audible, clarity, humble) terdapat dua indicator yang berhubungan dengan nilai p value< 0.05 dan tiga indicator lain memiliki p value>0.05 sehingga tidak ada hubungan dengan pemahaman pasien. Kesimpulan: Mayoritas responden berusia 21–30 tahun dan berjenis kelamin perempuan, serta menilai komunikasi radiografer telah efektif dengan tingkat pemahaman pasien yang tergolong baik. Hasil uji chi-square menunjukkan bahwa indikator clarity dan humble memiliki hubungan signifikan dengan pemahaman pasien, sedangkan indikator respect, empathy, dan audible tidak menunjukkan hubungan yang signifikan. Kata kunci : pemahaman pasien, public speaking, radiografi panoramik